Characteristic Features of the Design of a Magnetic System for a Betatron with a Compensating Winding - Kasyanov (Kas'yanov) V. A. Valery Alekseevich; Furman E. G. Edwin Gugovich; Chakhlov V. L. Vladimir Lukianovich; Chertov A. S. (2001, 2001)
Title screen